Analytical Study and Biological Evaluation of Drug Assays and Oxazolidinones Urea Derivatives - Reem Dabaibeh (International Journal of Medical Toxicology and Legal Medicine, 2025)
The increasing risk of antibiotic resistance highlights the vital need for the discovery of new antimicrobial drugs. Oxazolidinones are a potential relative of antibiotics that target the ribosomal 50S subunit and limit bacterial protein production. One significant category of oxazolidinones is urea derivatives, which can have improved bioactivity and decreased resistance. Novel oxazolidinone urea derivatives(NOUD)as effective antibacterial agents are the subject of this investigation, which involves their synthesis, analytical research, and biological assessment. Several chemical groups have been introduced into the center of the oxazolidinone structure throughout the multistep production of the oxazolidinone urea derivatives. To ensure the synthesized chemicals are structurally and chemically natural, analytical techniques such as nuclear magnetic resonance (NMR), mass spectrometry (MS), and high-performance liquid chromatography (HPLC) are used. The antibacterial efficacy of these compounds has been further improved by conducting molecular docking experiments to anticipate their binding affinity to bacterial ribosomes. As part of the biological examination, a panel of bacterial strains, both Gram-positive and Gram-negative, have been evaluated in vitro. Several of the produced oxazolidinone urea derivatives showed strong antibacterial action, especially against strains that are resistant to several drugs. The findings showed the minimum inhibitory concentration (MIC) values. In addition, the compounds’ safety profile was evaluated by performing cytotoxicity experiments on mammalian cells. Finally, the antibacterial activities of the newly produced oxazolidinone urea derivatives are encouraging, particularly in areas of resistance. To completely comprehend their potential as effective alternatives to antibiotic resistance, more optimization and preclinical research are necessary.